A new type of specialized morphophysiological dormancy and seed storage behaviour in Hydatellaceae, an early-divergent angiosperm family - Tuckett, R.; Merritt, D.; Rudall, P.; Hay, F.; Hopper, S.; Baskin, C.; Baskin, J.; Tratt, J.; Dixon, Kingsley (Oxford University Press, 2010)
Background and Aims: Recent phylogenetic analysis has placed the aquatic family Hydatellaceae as an early-divergent angiosperm. Understanding seed dormancy, germination and desiccation tolerance of Hydatellaceae will facilitate ex situ conservation and advance hypotheses regarding angiosperm evolution. Methods: Seed germination experiments were completed on three species of south-west Australian Hydatellaceae, Trithuria austinensis, T. bibracteata and T. submersa, to test the effects of temperature, light, germination stimulant and storage. Seeds were sectioned to examine embryo growth during germination in T. austinensis and T. submersa. Key Results: Some embryo growth and cell division in T. austinensis and T. submersa occurred prior to the emergence of an undifferentiated embryo from the seed coat ('germination'). Embryo differentiation occurred later, following further growth and a 3- to 4-fold increase in the number of cells. The time taken to achieve 50 of maximum germination for seeds on water agar was 50, 35 and 37 d for T. austinensis, T bibracteata and T. submersa, respectively. Conclusions: Seeds of Hydatellaceae have a new kind of specialized morphophysiological dormancy in which neither root nor shoot differentiates until after the embryo emerges from the seed coat. Seed biology is discussed in relation to early angiosperm evolution, together with ex situ conservation of this phylogenetically significant group. © The Author 2010.